2001
DOI: 10.1002/jnr.10080
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 Enhances myelin basic protein gene promoter activity

Abstract: The process of oligodendrocyte differentiation is a complex event that requires cell cycle withdrawal, followed by the activation of a specific transcriptional program responsible for the synthesis of myelin genes. Because growth arrest precedes differentiation, we sought to investigate the role of cell cycle molecules in the activation of myelin gene promoters. We hypothesized that the cell cycle inhibitor p27(Kip1), which is primarily responsible for arresting proliferating oligodendrocyte progenitors, may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…An alternative possibility is that some cell-cycle genes might affect the transcriptional machinery after the cells have exited from the cell cycle. This hypothesis is supported by evidence that links p27Kip to transcriptional activation of myelin genes (Miskimins et al, 2002) and p21Cip to oligodendrocyte differentiation independent of its role in cell-cycle regulation (Zezula et al, 2001). More recent studies further support an alternative role for the cell-cycle related molecule p57Kip2 as a modulator of the transcriptional network regulating oligodendrocyte differentiation (Dugas et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…An alternative possibility is that some cell-cycle genes might affect the transcriptional machinery after the cells have exited from the cell cycle. This hypothesis is supported by evidence that links p27Kip to transcriptional activation of myelin genes (Miskimins et al, 2002) and p21Cip to oligodendrocyte differentiation independent of its role in cell-cycle regulation (Zezula et al, 2001). More recent studies further support an alternative role for the cell-cycle related molecule p57Kip2 as a modulator of the transcriptional network regulating oligodendrocyte differentiation (Dugas et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…Because decreased expression of transcriptional inhibitors is important for the timing of progenitor differentiation and for myelin gene expression, we searched for a mechanism that regulates the expression levels of the inhibitors themselves. Studies from our group have identified that global deacetylation of histone H 3 is crucial for the decrease in transcriptional inhibitors of differentiation and that this occurs during the transition between cell-cycle exit and differentiation onset (Marin-Husstege et al., 2002;Shen et al, 2005). Therefore we proposed that global histone deacetylation is responsible for the decreased transcription of differentiation inhibitors.…”
Section: Timing Of Differentiation Caused By Disinhibition Of Late DImentioning
confidence: 87%
See 2 more Smart Citations
“…The importance of cell-cycle inhibitors in oligodendrocyte differentiation was further suggested by reports of alternative biological functions for these molecules. P27Kip, for instance, was identified as part of a transcriptional complex activating the MBP promoter (Miskimins et al 2002), as well as part of a complex with specific RNA-binding proteins like Qki (Larocque et al 2005). Despite these exciting findings, overexpression of cell-cycle inhibitors per se was not sufficient to induce differentiation (Tikoo et al 1998;Tang et al 1999) and suggested that additional events must be responsible for the differentiation of progenitors into mature oligodendrocytes.…”
Section: Model 3 Differentiation Consequent To Hdac-mediated Repressimentioning
confidence: 99%